Multinational Migration in the Global South: Complex and Non-linear Trajectories of Senegalese Migrants in Brazil - Jung, Philipp (2022)
A growing number of studies emphasise the non-linearity of migration. Aspirations and capabilities for multinational migration often develop or change during the migration process. These dynamics have mostly been analysed with regards to movements within the European Union or to countries in the so-called ‘Global North’. This chapter aims to broaden this focus by including movements in the context of South-South migration. It discusses multinational migration by Senegalese migrants in Brazil, which is both a destination and an origin of movements that connect a variety of countries and regions. It analyses the complex trajectories of Senegalese migrants from different social and educational backgrounds and focuses on how decisions to move again from one country to another develop and which factors influence the choice of destination. Through a multi-sited qualitative case study using interview and ethnographic methods with Senegalese migrants in four Brazilian cities – São Paulo, Praia Grande, Caxias do Sul and Passo Fundo – the research examines both already-occurred movements from Cape Verde and Argentina to Brazil and aspirations to migrate further to the ‘Global North’. The findings show that these multinational migrations are mostly driven by the desire for self-improvement – financial, professional or educational – and a hierarchy of desired destinations but also a result of suddenly emerging opportunities and mediation. The movements are facilitated through the multiple transnational ties with which Senegalese migrants are connected to different places. Furthermore, the study shows how Senegalese migrants acquire new migratory capital – for example in the form of another nationality, business activities or access to new networks – and how migration experiences influence onward migration aspirations and preparations, hereby drawing attention to the active learning process which migrants experience during their trajectory.